Pharmacist interventions for older adults with polypharmacy in an ambulatory geriatric clinic - Antonietta Paneccasio; Anna Bondar; Emily Fargo; Marcie Parker; Ardeshir Hashmi; Kenneth Koncilja; Gina Elder (Health Literacy and Communication Open)
Introduction Polypharmacy is a concern among older adults. An academic medical center in northeast Ohio currently has an outpatient geriatric medicine clinic with an embedded board-certified geriatric pharmacist who performs comprehensive medication management for older adults under a collaborative practice agreement. With polypharmacy as a primary referral reason, this pharmacist focuses on resolving drug-related problems (DRPs) and deprescribing.Aims The primary objective of this study was to describe the DRPs identified by the pharmacist for older adults referred for polypharmacy. Secondary objectives included: describing the DRPs resolved by the pharmacist, identifying the medications deprescribed, determining the frequency of additional outreach to other healthcare providers or patient caregivers, and characterizing any additional pharmacist interventions. This study aimed to determine the benefits of the expansion of geriatric pharmacy services.Methods This was a single-center, non-interventional, retrospective study. Patients were included if referred to geriatric ambulatory clinic pharmacy services for polypharmacy and completed an initial visit with the pharmacist between September 1, 2021, and August 31, 2022. Baseline characteristics and study outcomes were analyzed using descriptive statistics.Results A total of 137 patients were included for analysis, and a notable 82% of the study population had cognitive impairment documented. During the 137 initial visits with the pharmacist, 494 DRPs were identified, and more than half of these were resolved during the initial visit. All visits resulted in at least one pharmacist intervention. The most common DRP identified was unnecessary drug therapy (38.6%). Of the 313 medications identified as eligible for deprescribing, about half were deprescribed by the pharmacist during the initial visit. Of the 133 additional pharmacist interventions, medication education was the most common (52%).Discussion The results of this study emphasize the benefit of comprehensive medication management with a focus on deprescribing for an older adult population with polypharmacy, the majority of whom had cognitive impairment.